Corporate Social Responsibility Practices in the Top Ten Indian Companiesand Its Impact on Community Development - Bhukya, Veerabhadram (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
The study presents contemporary Corporate Social Responsibility Practices (CSRPs) in literature. The basic purpose and aim of the study are to describe and investigate the broad categories of Corporate Social Responsibility Practices (CSRPs) of the top 10 Indian companies where it operates the business and their response towards the surrounding community development environment. This study also tries to build the relationship between Corporate Social Responsibility Practices and their impact on community development and the well-being of a community. The present study has adopted a secondary source of data, that is used to analyze the data based on archival data sources. Finally, the findings of this study will show that Corporate Social Responsibility Practices (CSRPs) positively influence and impact community development and well-being. Also, the results of the study will have a significant and practical implication on societal progressive development and future research on Corporate Social Responsibility (CSRPs) and Community Development (CD).